Research with religious leaders: ethical and methodological issues - Machado, Maria das Dores Campos (FCL-UNESP Laboratório Editorial, 2013)
This article analyses the methodological approach of two qualitative research projects intended to get to know religious leaders perceptions and attitudes on a number of contemporary problems. Involving social agents from different traditions and groups within the same religion, those surveys faced several difficulties and required a lot of creativity from researchers to find solutions in order not to affect the understanding of the problem under the analysis. Divided into four sections, I begin with a brief introduction on the current situation of comparative research in religious studies. Along the second section, I review a research on opinions and initiatives of religious leaders about multiple sexualities. Along the third section, I discuss the methodology and challenges faced in a research with Pentecostal leaders on social, economic, cultural and political issues. By the last section, I present some considerations on the complexity of researches with wellknown personalities in the subfield of sociology of religion.